2019
DOI: 10.3390/antibiotics8030097
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibiotic Resistance Profile and Biofilm Production of Staphylococcus aureus Isolates Derived from Human Specimens and Animal-Derived Samples

Abstract: Background: The diffusion of antimicrobial resistance is a significant concern for public health worldwide. Staphylococcus aureus represents a paradigm microorganism for antibiotic resistance in that resistant strains appear within a decade after the introduction of new antibiotics. Methods: Fourteen S. aureus isolates from human specimens and twenty-one from samples of animal origin, were compared for their antimicrobial resistance and biofilm capability. In addition, they were characterized at the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…When the biochemical analysis was not exhaustive, amplification and sequencing of the 464 bp fragment of the 16S rDNA were carried out. An aliquot (2 µL) of the bacterial lysate, prepared as previously described [47], was used to amplify the 464 bp internal fragment of the 16S rDNA using One Taq DNA polymerase (NEB), using primer pairs and the corresponding annealing temperatures listed in Table 4. After confirmation through agarose (1% w/v) gel electrophoresis, the polymerase chain reaction (PCR) products were purified and sequenced at Macrogen Inc. (Seoul, Korea, sequencer).…”
Section: Bacterial Isolationmentioning
confidence: 99%
“…When the biochemical analysis was not exhaustive, amplification and sequencing of the 464 bp fragment of the 16S rDNA were carried out. An aliquot (2 µL) of the bacterial lysate, prepared as previously described [47], was used to amplify the 464 bp internal fragment of the 16S rDNA using One Taq DNA polymerase (NEB), using primer pairs and the corresponding annealing temperatures listed in Table 4. After confirmation through agarose (1% w/v) gel electrophoresis, the polymerase chain reaction (PCR) products were purified and sequenced at Macrogen Inc. (Seoul, Korea, sequencer).…”
Section: Bacterial Isolationmentioning
confidence: 99%
“…The ability to control bacterial growth and colonization is of extreme practical importance in several fields, including prevention of food contamination in the food chain, in healthcare and even in the protection of cultural heritage to reduce biodeterioration processes . In the last years, the emergence of multi‐drug resistant strains occurred in several animals and environments, including wild and uncontaminated ones .…”
Section: Figurementioning
confidence: 99%
“…In the last years, the emergence of multi‐drug resistant strains occurred in several animals and environments, including wild and uncontaminated ones . One of the most frequent antibiotic resistant strain causing food poisoning is the Gram positive Staphylococcus aureus …”
Section: Figurementioning
confidence: 99%
“…This assumption is supported by the report of Wójcik et al, 2018 [ 35 ] that demonstrated the incorporation of perfluorinated compounds into model membranes resembling those typical to Gram-negative bacteria. Antibacterial activity was also tested against S. aureus ATCC 25923 and S. aureus ATCC 33862, two pathogenic, toxigenic and biofilm producer strains, frequently associated with both human and animal infections [ 2 ] and we found that both complexes were active in inhibiting the growth of both the strains with complex 1 more performing than complex 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial infections in clinical and veterinary environments can frequently be due to different MDR bacterial strains, such as Staphylococcus aureus (S. aureus) and Escherichia coli ( E. coli ) , etc. [ 2 , 3 ]. In the frame of our study, we have previously synthesized, characterized and investigated the biological activity of Pt(II) complexes with 2-(5-perfluoropropyl)-1,2,4-oxadiazole-3yl)-pyridine ( pfpop ), 2-(5-perfluoroheptyl-1,2,4-oxadiazole-3yl)-pyridine ( pfhop ), 2-(3-perfluoropropyl-1-methyl-1,2,4-triazole-5yl)-pyridine ( pfptp ), and 2-(3-perfluoroheptyl-1-methyl-1,2,4-triazole-5yl)-pyridine ( pfhtp ) ligands, finding interesting data concerning both antitumor and antimicrobial activity [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%